PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MENGGUNAKAN METODE KERJA KELOMPOK SISWA KELAS II SEKOLAH DASAR NEGERI 18 SUNGAI KAKAP - Yohani, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstrak: Tujuan penelitian ini secara umum yaitu untuk meningkatkan hasil belajar siswa dalam pembelajaran IPA menggunakan metode kerja kelompok. Metode penelitian ini adalah metode deskriptif dengan bentuk penelitian tindakan kelas (Classroom Action Research). Penelitian ini dilaksanakan di Sekolah Dasar Negeri 18 Sungai Kakap Kabupaten Kubu Raya dengan subyek penelitiannya adalah 19 siswa kelas II. Hasil belajar siswa dengan menerapkan metode kerja kelompok pada pembelajaran Ilmu Pengetahuan Alam pada setiap siklusnya mengalami peningkatan. Nilai rata-rata hasil belajar siswa pada base line yaitu 47,36. Nilai rata-rata pada siklus I sebesar 56,84 dan pada nilai rata-rata pada siklus II sebesar 83,68. Dari base line ke siklus II terjadi peningkatan sebesar nilai rata-rata sebesar 36,32 dan ketuntasan belajar sebesar 78,9%. Sedangkan kemampuan guru dalam merencanakan pembelajaran pada siklus I dan siklus II secara berurutan sebesar 2,80 dan 3,80 sementara kemampuan guru dalam melaksanakan pembelajaran siklus I dan siklus II sebesar 2,90 dan 3,90. Â Kata Kunci : Hasil Belajar, Pembelajaran IPA, Metode Kerja Kelompok. Abstrak: The purpose of this research in general is to improve student learning outcomes in science learning using group work method. This research method is descriptive method with the form of classroom action research (Classroom Action Research). The research was conducted at the State Elementary School 18 Kubu Raya Sungai snapper with the subjects of the study were 19 students of class II. Data collection technique used was direct observation techniques. Tools such as data collectors to observe the observation sheet student learning activities, IPKG 1 to observe teachers in planning lessons, and IPKG 2 to observe teachers in implementing the learning. Data were analyzed using the average formula and the percentage of students learning completeness. Student learning outcomes by applying methods of group work at study Natural Sciences at each cycle has increased. The average value of student learning outcomes at baseline, namely 47.36 with learning completeness 10.5%. The average value in the first cycle of 56.84 with learning completeness of 47.3% and the average value in the second cycle of 83.68 with learning completeness 89.4%. From the base line to the second cycle an increase of the average value of 36.32 and amounted to 78.9% completeness study. While the ability of teachers to plan learning in the first cycle and the second cycle in sequence by 2.80 and 3.80 while the learning ability of teachers to carry out the first cycle and the second cycle of 2.90 and 3.90. Â Key word: Results Learning, Learning science, Group Work Method